ID 303 – Transcranial direct current stimulation (tDCS) in patients with frontotemporal dementia. Issue 3 (March 2016) - Ferrucci, R.; Ruggiero, F.; Vergari, M.; Mameli, F.; Colangelo, F.; Arighi, A.; Scarpini, E.; Priori, A.
Abstract : Objective: To assess neurophysiological and behavioral effects of tDCS in patients with Frontotemporal Dementia (FTD). Methods: 11 patients (aged 63–77) diagnosed as having FTD were recruited. We delivered bilateral frontotemporal anodal (2 mA, 20 min, five consecutive days) and sham tDCS, in two separate cycles at intervals of at least 1 month. In each cycles, the Neuropsychiatric Inventory (NPI) and EEG were administered before (baseline T0), after the last tDCS cycle on day 5 (T1), one week (T2) and one month (T3) after the end of the treatment. Results: Anodal but not sham tDCS decreased NPI total scores by 7 ± 2 points at T1 ( p = 0.025) and 6 ± 3 points at T2 ( p = 0.024) and induced a reduction of delta EEG power spectrum over frontotemporal cortex by 60 ± 27% at T3 ( p = 0.004). We found a significant negative correlation between NPI and EEG delta power at T2 ( P < 0.001, r = −0.87). Conclusions: Our results show an improvement of behavioral score in FTD patients after repeated anodal tDCS correlating with the reduction of delta EEG power spectrum activity in the frontotemporal areas. Key Message: Our finding prompts studies using repeated tDCS treatment, in a large sample size, in conjunction with other therapeutic interventions for the management of FTD patients.